Analisis Penerapan Strategi Pemasaran Terhadap Jumlah Tabungan pada PT. Bank Sumut Syariah Kantor Cabang Pembantu Marelan Raya - Rani Nasution; Rahmat Kurniawan (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to determine the application of marketing strategies to the number of savings at PT. Bank Sumut Syariah Sub-Branch Office Marelan Raya, knowing the SWOT analysis in the application of marketing strategies to the number of savings, and knowing opportunities and challenges to the amount of savings at PT. Bank Sumut Sharia Sub-Branch Office of Marelanfood. Research is a qualitative type of research, the method of this research arises because there is a change in paradigm in viewing a reality or phenomenon. The data collection techniques use observation, interviews, and documentation. For data analysis techniques use data collection, data reduction, data presentation, and conclusion drawings, while triangulation is triangulation of sources, techniques, and time. The results of this study indicate that the marketing strategy of savings products in increasing the number of savings at PT. Bank Sumut Syariah KCP Marelan Raya is done with a 7P marketing mix, namely Product (product) Place (place), Price (price), Promotion (promotion), People (people), process (process), and physical evidence (physical evidence The challenge of marketing strategies is the lack of knowledge from the public about what products are offered at PT. Bank Sumut Sharia Parield Assistant Branch Office and its opportunities namely PT. Bank Sumut Syariah KCP Marelan Raya further increases socialization so that the public knows the product of PT. Bank Sumut Sharia Sub-Branch Office of Marelanfood.